Do inconsistent mental models impact performance? Moderating effects of managerial interpretation and practice sets - Zhao, Ying; Gao, Yuan; Hao, XiLing; Ren, FangFang (Frontiers in Psychology, 2023)
Deviant cognition referring to team members’ different understanding of goals or rules, results in inconsistent mental models among the team. Although previous studies have examined the negative effects of inconsistent mental models on deviant behavior and performance in the workplace, they have failed to consider their positive effects and moderating mechanisms, thus limiting our understanding of how to manage inconsistent mental models and deviant cognition. To address this research gap, this study builds on the interpretation and information processing theory, which regards mental models as the result of information processing, especially involving interactions where interpretation of the information is required. The study initially recruited 174 team managers as participants to identify instances of managerial interpretation. The team managers’ interpretation modes were then categorized into four types (absorb, shift, limit, and explore), and a questionnaire was developed to measure them. The moderating effects of the modes on execution and innovation performance were also examined. Matched data were then collected from interviews with 104 team managers and 312 of their team members. The regression results showed that the absorb, shift, and limit interpretation modes, as well as the practice sets involving managers and members, attenuated the negative relationship between inconsistent mental models and execution performance. The explore interpretation mode and the practice sets enhanced the positive relationship between inconsistent mental models and team innovation. The findings of this study help to understand the cognitive level of deviance in teams and the moderating effects of managerial interpretation on the relationship between deviant cognition, or inconsistent mental models, and performance, suggesting the need to study and utilize the positive roles of inconsistent mental models or deviance through managerial interpretation. The results also call for firms to train managers’ interpretation skills and design close working links with team members.